Establishing an experimental model for canine atopic dermatitis through epicutaneous application of Dermatophagoides farinae - Kim, Sang-Won; Kim, Jung-Hyun (Frontiers in Veterinary Science, 2022)
There is no established protocol for the development of an experimental canine atopic dermatitis model in laboratory beagles. This study aimed to establish an experimental model that mimics spontaneous canine atopic dermatitis (CAD) clinically, immunologically, and microbiologically, by repeated epicutaneous applications of mite antigens and to describe the entire process including sensitization and provocation in detail for reproducibility. Six intact male laboratory beagle dogs aged 14 months were included in this study. During the sensitization and provocation phase, the house dust mite (HDM) paste consisted of Dermatophagoides farinae (Der f) and mineral oil, which was applied focally to the 10 × 10 cm area of the right groin as evenly as possible. Further, 120 mg of Der f was applied to each dog twice a week for 12 weeks during the sensitization phase and 25 mg and 120 mg was applied to each dog for the first 2 weeks and subsequent 2 weeks, respectively, during the provocation phase. Thereafter, the applied area was covered with a dressing. Skin lesions including erythema, hyperpigmentation, excoriation, and lichenification were induced and exacerbated gradually through the experimental time course in all six dogs. The canine atopic dermatitis extent and severity index (CADESI) score and transepidermal water loss (TEWL) significantly increased after sensitization and provocation. IL-13 and IL-31 levels increased significantly after provocation as a result of the activation of the T helper-2 (Th2) response. On the contrary, the IL-10 levels decreased significantly after sensitization, which suggested a suppression of Tregs activity. After the completion of provocation, skin microbiome analysis showed that Firmicutes was the most abundant phylum, which indicated bacterial dysbiosis. This study demonstrated that epicutaneous application of HDM in beagle dogs resulted in the elevation of serum HDM-specific IgE levels and clinical atopic scores, a high TEWL, and microbiome dysbiosis resembling spontaneous CAD. These results suggest that this tailored protocol of epicutaneous exposure to Der f may provide support for the development of the experimental CAD model in laboratory beagles.